(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2014)
Introduction: In developing countries more than 90% infants are born with low birth weight (LBW). In Bangladesh the incidence is about 30%. Newborn baby has got a definite difference in metabolic profile from the adult; this difference is much more pronounced in case of LBW newborn. Infants born prematurely or following intrauterine malnutrition may develop abnormally low plasma glucose concentration for a prolonged period as a result of the failure to adapt a metabolic and endocrine response. Glucose is an essential nutrient for the brain. Abnormally low levels (hypoglycaemia) can cause encephalopathy and have the potential to produce long-term neurological injury. Adequate knowledge about neonatal physiology is important in the management of LBW neonates in the neonatal nursery specially in the first 48 hours of life as most of the neonatal deaths occur in this critical period of time. Objectives: To evaluate the clinical features of hypoglycaemic low birth weight (LBW) neonates in the first 48 hours of life. Methods: This cross-sectional study was conducted on 56 LBW neonates in the inpatient departments of Paediatrics and Obstetrics of Combined Military Hospital (CMH), Dhaka between 15th September 2010 to 14th March 2011. LBW (Weight <2500gm) neonates, both term and preterm, from birth to 48 hours of age and who were well at the time of blood collection were included in this study. After enrollment of the newborn, with all aseptic precaution blood samples were taken from cord (as basal) at birth, from venous blood at 2 hours and then from capillary blood at 4 hours, in between 12-24 hours and in between 24-48 hours by heel prick from each case . Cord and capillary blood glucose were measured by using Accu-Check-Active- glucometer. Blood glucose concentrations less than 2.6 mmol/L irrespective of weight and gestational age were considered as low for the purpose of analysis. Results: It was revealed from the study that the mean birth weight was 1.77 gm mean gestational age was 36.09 weeks. 30 ( 53.57% ) were intrauterine growth retarded (IUGR) and 26 (46.43% ) were appropriate for gestational age (AGA). Out of thirty IUGR, 24 (51.79%) infants had low blood glucose (<2.6 mmol/L) levels. Twenty-two (75.86%) of 29 low birth weight infants showed low blood glucose at one of the five time points, 07 (17.07%) had low values on two hypoglycemia at 12-24 hours of age. The mean blood glucose concentration in LBW infants were 4.03 mmol/L at birth (cord), 2.33mmol/L at 2 hours, 2.96mmol/L, at 4 hours 3.14mmol/L, at 1224hours and 3.43mmol/ L at 2448hours of age. In the first 48 hours, the lowest blood glucose (mean) concentrations were found at 2 hours after delivery. Hypoglycaemia was most common among the preterm intrauterine growth retarded (IUGR) neonates at 2 hours after delivery. Most 23 (79.31%) of the hypoglycaemic infants were asymptomatic and 6 (20.69%) had symptoms. Early feeding prevents hypoglycaemia and appears to influence subsequent glucose values. Among the manifestations jitteriness, hyperalert, tachypnoea, high pitched cry, lethargy, apnoea and poor feeding were observed. Conclusion: The study findings may be helpful in the management of LBW neonates with hypoglycaemia and will encourage the mother in initiation of feeding immediately after delivery. DOI: http://dx.doi.org/10.3329/jafmc.v9i1.18726 Journal of Armed Forces Medical College Bangladesh Vol.9(1) 2013: 49-56